Pancreatic Tuberculosis: A Case Report - Shrestha, Richa; Sharma, Anup; Baidya, Pooja; Adhikari, Milan (Journal of Nepalgunj Medical College, 2023)
Introduction: Pancreatic tuberculosis is a rare condition even in countries with high tuberculosis prevalence. It can mimic pancreatic carcinoma in symptoms and radiological studied. Extrapulmonary tuberculosis is common in organs like liver, bowel, spleen, peritoneum and mesenteric lymphnodes than pancreas which is suggestive to have protective role because of its secretions. Case presentation: A 71 year female presented with abdominal pain with no history of pulmonary tuberculosis. Radiological studies suggested pancreatic carcinoma. Laparotomy was performed and Whipple’s pancreatoduodenctomy specimen was sent to histopathology department along with regional lymphnodes. On gross examination, a mass was noted in uncinate process. Histopathological examination revealed chronic inflammatory granulomatous reaction with Langhan’s giant cells and areas of caseous necrosis. The Ziehl Neelsen (ZN) stain confirmed the presence of acid-fast bacilli diagnosing pancreatic tuberculosis. Conclusion: Tuberculosis should be considered as one of the differential diagnosis of pancreatic masses, especially in immunocompromised patients, as the outcome to antituberculosis treatment is very favorable.